1985
DOI: 10.1246/cl.1985.1743
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Permeation Through Perovskite-Type Oxides

Abstract: The rate of oxygen permeation through La1−xSrxCo1−yFeyO3−δ was found to increase with an increase in Sr or Co content, showing that the permeability was mainly controlled by the amount of oxygen vacancies. The results obtained indicate that mixed conductive perovskite-type oxides are promising materials for oxygen permeation at elevated temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
524
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(538 citation statements)
references
References 4 publications
9
524
2
3
Order By: Relevance
“…The membrane tube with a smaller inner diameter possesses much better oxygen permeability, which suggests that oxygen-permeable membranes in hollow fiber configurations should perform well and they should be developed to meet the needs of air separation in industry. molar flow rate of oxygen at the exit of the tube side (mol/s) N P molar flow rate of the gases in membrane lumen (mol/s) N P,out molar flow rate of the gases at the exit of the tube side (mol/s) N R molar flow rate of the gases in the shell side (mol/s) N R,out molar flow rate of the gases at the exit of shell side (mol/s) P 1 oxygen partial pressure in the shell side (Pa (atm)) P 1,in oxygen partial pressure in the feed (Pa (atm)) P 1,out oxygen partial pressure at the exit of shell side (Pa (atm)) P 2 oxygen partial pressure in the tube side (Pa (atm)) P S total pressure in the shell side (Pa (atm)) P S,max maximum pressure in the shell side (Pa (atm)) P T total pressure in the tube side (Pa (atm)) P T,in total pressure in the inlet of the membrane tube (Pa (atm)) P V vacuum pressure in the tube side (Pa (atm)) R gas constant (83.147 ×10 5 Pa cm 3 /(mol K) (82.06 atm cm 3 /(mol K))) S area of a membrane tube (cm 2 ) T operating temperature ( • C, or K in Eq. (9)) X in fraction of O 2 in a feed gas in the shell side …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane tube with a smaller inner diameter possesses much better oxygen permeability, which suggests that oxygen-permeable membranes in hollow fiber configurations should perform well and they should be developed to meet the needs of air separation in industry. molar flow rate of oxygen at the exit of the tube side (mol/s) N P molar flow rate of the gases in membrane lumen (mol/s) N P,out molar flow rate of the gases at the exit of the tube side (mol/s) N R molar flow rate of the gases in the shell side (mol/s) N R,out molar flow rate of the gases at the exit of shell side (mol/s) P 1 oxygen partial pressure in the shell side (Pa (atm)) P 1,in oxygen partial pressure in the feed (Pa (atm)) P 1,out oxygen partial pressure at the exit of shell side (Pa (atm)) P 2 oxygen partial pressure in the tube side (Pa (atm)) P S total pressure in the shell side (Pa (atm)) P S,max maximum pressure in the shell side (Pa (atm)) P T total pressure in the tube side (Pa (atm)) P T,in total pressure in the inlet of the membrane tube (Pa (atm)) P V vacuum pressure in the tube side (Pa (atm)) R gas constant (83.147 ×10 5 Pa cm 3 /(mol K) (82.06 atm cm 3 /(mol K))) S area of a membrane tube (cm 2 ) T operating temperature ( • C, or K in Eq. (9)) X in fraction of O 2 in a feed gas in the shell side …”
Section: Discussionmentioning
confidence: 99%
“…Teraoka et al reported very high oxygen permeation fluxes through the perovskite oxide based on La 1−x A x Co 1−y Fe y O 3−δ [2][3][4]. Since then, there have been many efforts on the research of mixed-conducting membranes [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s when mixed-conducting ceramic membranes were introduced [3][4][5][6], extensive research has been performed to improve oxygen permeation rates [7][8][9][10][11][12][13]. In the course of these experimental activities, a reactive gas such as methane has been employed on the permeate side to increase the chemical potential gradient by consuming the permeated oxygen and to maintain the membrane temperature, and thus to enhance oxygen permeation rates.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop a membrane exhibiting high oxygen flux, better mechanical strength and good phase stability in a reducing atmosphere, extensive studies have been conducted in more than 20 laboratories worldwide (Teraoka et al, 1985;Teraoka et al, 1988;Diethelm et al, 2003Yan et al, 2010Kim et al, 1997;Ishihara et al, 2000;Schiestel et al, 2005;Liu et al, 2005;Li et al, 2006;Tan et al, 2005). Among the MIECs, Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF) is considered to be one of the most promising materials because its membranes show high oxygen permeation fluxes and excellent cathode performance for SOFCs (Shao and Haile, 2004;Shao et al, 2000;McIntosh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%